Baseline values for Quantra® QPlus® in healthy pregnant women at term and comparison to standard laboratory coagulation values: a prospective observational study - Suthawan Anakmeteeprugsa; Antonio Gonzalez-Fiol; Angelique Garay; Hung-Mo Lin; Zili He; Aymen Alian (BMC Pregnancy and Childbirth)
Abstract Background Hypofibrinogenemia is associated with progression from moderate to severe postpartum hemorrhage (PPH). Early recognition and replacement of fibrinogen are emphasized during the management of PPH. The Quantra® QPlus® System, a novel point-of-care viscoelastic testing (POCVT) device, has been designed to provide rapid assessment of hemostasis. We aimed to evaluate the correlation between Quantra parameters and standard laboratory coagulation tests, and to establish baseline Quantra values in healthy term pregnant women. Methods Healthy pregnant women in labor or scheduled for elective cesarean delivery (CD) were enrolled in our prospective observational study. Blood samples for Quantra and standard laboratory coagulation tests were taken simultaneously. Quantra values, standard laboratory coagulation test, time of blood collected, and time to the result were recorded. We compared the baseline values between CD and labor group using a t-test, and the correlation between Quantra and standard laboratory coagulation test was calculated using partial Pearson correlation. Results 170 healthy pregnant women were included; 126 cases were in the CD group, and 44 patients were in the labor group. We found a strong correlation between Quantra Fibrinogen contribution to Clot Stiffness (FCS) and fibrinogen level (r = 0.67). The median [interquartile range] time of fibrinogen results by Quantra was 36 [28, 48] minutes faster than the standard laboratory coagulation tests. Baseline ranges for Quantra values, which were not significantly different between the two groups, demonstrated hyperfibrinogenemia during pregnancy. Conclusion Quantra is a novel POCVT device that rapidly provides coagulation status in pregnant women. The strong correlation between FCS and fibrinogen level can be helpful for early recognition of hypofibrinogenemia for the management of PPH.